MACROECONOMIC ASPECTS OF SUSTAINABLE DEVELOPMENT OF THE ECONOMY - S. A. Bakhodurova (Вестник университета)
The essence and indicators of a concept of sustainable development of economy have been considered. Dynamics of an indicator of social and economic development of the region (gross regional product) has been analyzed and the stability indicator has been сalculated. Macroeconomic aspects of unstable development of economy have been revealed through imbalances of inflows and outflows in the two-sector, closed and opened economic systems. The reasons and consequences of disproportions of an economic system have been identified. Measures and directions of state policy in the field of stimulating the development of small and medium-sized businesses, creating a favorable business environment, stimulating export-oriented production, improving migration policies, which will reduce these imbalances, have been proposed. Accounting of regularity of macroeconomic interrelations will allow you to assess a situation of economic systems, and studying of the existing imbalances will promote creation of the mechanism of their regulation.